„Państwo Islamskie” i jego wpływ na aktualne bezpieczeństwo międzynarodowe - Machniak, Arkadiusz (Polityka i Społeczeństwo, 2020)
The Islamic State was established as a result of many political, social and economic factors. It is currently the strongest terrorist structure in the world, which has support among the Islamic community across the globe. IS is a creation, which destabilizes the situation in the Middle East and threatens international security. Only the creation of a single international coalition sharing a common military and political policy against the IS can lead to the neutralization of this threat.